Hypertension Risk Factor Control Effort In Post Stroke Patients - Yosi Suryarinilsih; Hendri Budi; Netti Netti; Wiwi Sartika (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Post-stroke patients have risk factors for recurrent stroke. The main risk factor is hypertension. The purpose of this community service activity is to improve the ability of the community, especially post-stroke patients, to control hypertension as a risk factor for recurrent stroke through identification of risk factors, health education and the application of light activity and deep breathing exercises. Before education is given, post-stroke patients and their families are given prestest first and after education, posttest returns to evaluate the patient's understanding. The results of the activity, there was a significant difference between the knowledge before and after being given education to post-stroke patients and their families with p value <0.05. To the head of the room and the neuroscientific nurse, dr. M. Djamil Padang can continue the activity of identifying recurrent stroke risk factors and health education related to control of recurrent stroke risk factors in post-stroke patients by involving the Health Promotion (Promkes) department of Dr. M. Djamil Padang.